Early-type galaxy density profiles from IllustrisTNG – I. Galaxy correlations and the impact of baryons. Issue 4 (29th November 2019) - Wang, Yunchong; Vogelsberger, Mark; Xu, Dandan; Mao, Shude; Springel, Volker; Li, Hui; Barnes, David; Hernquist, Lars; Pillepich, Annalisa; Marinacci, Federico; Pakmor, Rüediger; Weinberger, Rainer; et al.
ABSTRACT: We explore the isothermal total density profiles of early-type galaxies (ETGs) in the IllustrisTNG simulation. For the selected 559 ETGs at z = 0 with stellar masses 10^10.7 M_ M_* 10^11.9 M_, the total power-law slope has a mean of 〈γ′〉 = 2.011 ± 0.007 and a scatter of σ _γ ^′ = 0.171 over the radial range 0.4–4 times the stellar half-mass radius. Several correlations between γ′ and galactic properties including stellar mass, effective radius, stellar surface density, central velocity dispersion, central dark matter fraction, and in situ -formed stellar mass ratio are compared to observations and other simulations, revealing that IllustrisTNG reproduces many correlation trends, and in particular, γ′ is almost constant with redshift below z = 2. Through analysing IllustrisTNG model variations, we show that black hole kinetic winds are crucial to lowering γ′ and matching observed galaxy correlations. The effects of stellar winds on γ′ are subdominant compared to active galactic nucleus (AGN) feedback, and differ due to the presence of AGN feedback from previous works. The density profiles of the ETG dark matter haloes are well described by steeper than NFW profiles, and they are steeper in the full physics (FP) run than their counterparts in the dark matter-only (DMO) run. Their inner density slopes anticorrelate (remain constant) with the halo mass in the FP (DMO) run, and anticorrelate with the halo concentration parameter c 200 in both the types of runs. The dark matter haloes of low-mass ETGs are contracted whereas high-mass ETGs are expanded, suggesting that variations in the total density profile occur through the different halo responses to baryons.